1999
DOI: 10.1177/089198879901200208
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Serum Anticholinergic Activity in the Assessment of Elderly Patients with Delirium

Abstract: To evaluate the importance of serum anticholinergic activity (SAA) in elderly patients who developed delirium following hospital admission, we performed a cross-sectional study with consecutively referred inpatients in a university geriatric medical ward. Sixty-one patients aged 66 to 95 years (mean age: 79.2+/-11.6; 54% females) were recruited. Delirium was assessed by means of the Confusion Assessment Method, SAA determination, questionnaire for current drug treatment, past medical history and clinical exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
1
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 23 publications
3
43
1
3
Order By: Relevance
“…The SAA levels reported in the literature were measured with comparable methods but produced widely differing results that appear to be due to the different patient populations studied. In normal young healthy individuals who are not hospitalised, SAA levels are undetectable or low [25]; surgical patients and the elderly showed the highest SAA values [11,26,27]. However, some workers have found much lower SAA levels in similar patient groups [13,28].…”
Section: Discussionmentioning
confidence: 99%
“…The SAA levels reported in the literature were measured with comparable methods but produced widely differing results that appear to be due to the different patient populations studied. In normal young healthy individuals who are not hospitalised, SAA levels are undetectable or low [25]; surgical patients and the elderly showed the highest SAA values [11,26,27]. However, some workers have found much lower SAA levels in similar patient groups [13,28].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the prevalence of delirium in this study [96] jumped from 8% to 62% when comparing patients with the highest and lowest SAA levels (top and bottom 20th percentile). Mussi and colleagues [104] also reported a link between the incidence of delirium and SAA levels (P!.004) while controlling for other risk factors such as the use of antipsychotics and benzodiazepine. Additionally, all of the patients who had SAA profiles greater than 20.0 pmol/mL [104] were found to be delirious as defined by the Confusion Assessment Method for the ICU [106].…”
Section: The Cholinergic Hypothesismentioning
confidence: 99%
“…The assay required to measure SAA was first developed in 1980 by Tune and Coyle [105]. Following this development, several clinical investigations found relationships between SAA levels and the development of delirium [102][103][104]. Thomas and colleagues [102] reported that SAA levels were higher in delirious patients when compared with non-delirious individuals in a sample of surgical patients in the ICU.…”
Section: The Cholinergic Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…Наиболее часто причиной делирия считают наруше-ние функционирования холинергической системы [29], и это обосновывается целым рядом факторов [35][36][37][38][39][40][41]. Есть также упоминание [42] о нарушении функционирования дофаминергической системы, а также о дисбалансе дофаминовой и холинергиче-ской систем.…”
Section: этиология и патогенезunclassified